2012
DOI: 10.1536/ihj.53.54
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Mononuclear Cells Expressing β-Actin Through the Adventitia into Media and Intima in Coronary Arteriogenesis and Venogenesis in Ischemic Myocardium

Abstract: SummaryIt was previously thought that arteriogenesis and venogenesis are induced not only by proliferation of vessel-resident smooth muscle cells (SMCs) and endothelial cells (ECs) but also by migration of their precursors. However, it is not well understood through what route(s) the precursors migrate into the existing vessels.We examined through what route or routes circulating mononuclear cells expressing β-actin (β-MNCs), which we identified in canine coronary vessels, migrate into coronary vessel walls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…They contained CD 34 , indicating a bone marrow origin. β-MNCs however did not contain α-SMA, CD 31 , and vimentin as shown in our previous study [22]. …”
Section: Circulating β-Mncs In the Coronary Lumensupporting
confidence: 67%
See 4 more Smart Citations
“…They contained CD 34 , indicating a bone marrow origin. β-MNCs however did not contain α-SMA, CD 31 , and vimentin as shown in our previous study [22]. …”
Section: Circulating β-Mncs In the Coronary Lumensupporting
confidence: 67%
“…In a previous study using the same infarction model in beagles, we found that β-MNCs migrate into the interstitial space and then from outside of the adventitia into the media of the existing arterioles or arteries to become SMCs by loosing β-actin and acquiring α-SMA, and into the intima to become ECs by acquiring CD 31 , indicating that the β-MNCs are multipotent vascular progenitor cells [22].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations